Edukasi zero Waste Lifestyle Dalam Mewujudkan Lingkungan Bebas Sampah di Kelurahan Perhentian Marpoyan - Zulmeliza Rasyid; Novita Rany; Agus Mandar; Budijono Budijono; Ali Asfar; Indra Suandy (Jurnal Medika: Medika, 2026)
Zero-waste lifestyle education is a strategic approach to addressing the waste problem in Perhentian Marpoyan Village. With increasing population and economic activity, the volume of waste generated is increasing, threatening environmental cleanliness and health. This study aims to provide public understanding of the importance of adopting a zero-waste lifestyle, focusing on the principles of Reduce, Reuse, and Recycle (3R). The methods used included outreach and hands-on practice in waste management. Health education was conducted in Perhentian Marpoyan Village. The media used for the education included laptops, n-focus, and leaflets. The education methods used were lectures and question-and-answer discussions. The results of this education showed increased environmental awareness and active community participation in waste management. Participants' knowledge increased from 45% to 80%, demonstrating the effectiveness of the zero-waste lifestyle education method. Through a series of workshops, education sessions, and awareness campaigns, the community was encouraged to change their daily consumption patterns and behaviors. Thus, implementing a zero-waste lifestyle is expected to create a cleaner and healthier environment and create a community committed to sustainability.